cMET: a prognostic marker in papillary renal cell carcinoma? - Erlmeier, Franziska; Bruecher, Benedict; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Human pathology, 2022)
The tyrosine-protein kinase c-Met plays a decisive role in numerous cellular processes, as a proto-oncogene that supports aggressive tumor behavior. It is still unknown whether c-Met could be relevant for prognosis of papillary RCC (pRCC). Specimen collection was a collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from 197 and 110 patients with type 1 and 2 pRCC, respectively. Expression of cMET was determined by immunohistochemistry. In total, cMET staining was evaluable in of 97 of 197 type 1 and 63 of 110 type 2 pRCC cases. Five-year overall survival revealed no significant difference in dependence of cMET positivity (cMET− vs. cMET+: pRCC type 1: 84.8% vs. 80.3%, respectively [p = 0.303, log-rank]; type 2: 71.4% vs. 64.4%, respectively [p = 0.239, log-rank]). Interestingly, the subgroup analyses showed a significant difference for cMET expression in T stage and metastases of the pRCC type 2 (p = 0.014, p = 0.022, chi-square). The cMET-positive type 2 collective developed more metastases than the cMET-negative cohort (pRCC type 2 M+: cMET−: 2 [4.3%] vs. cMET+: 12 [19%]). cMET expression did not qualify as a prognostic marker in pRCC for overall survival.
Gesehen am 16.03.2022